Design Concept of Dynamic-Adaptive Reconfigurable Wireless Sensor Node (DARWiSeN) - C. Bambang Dwi Kuncoro; M. Anda Falahuddin (Universitas Ahmad Dahlan, 2014)
This paper describe the proposed design concept of wireless sensor node named Dynamic-Adaptive Reconfigurable Wireless Sensor Node (DARWiSeN), with special emphasis on the design principles and functionality. The design concept is targeted to a wireless sensor node prototype that has ability to adapt various applications and situation with a minimal redesign effort through concept of reconfigurable hardware and modularity approach. Both the hardware and software components are detailed, together with experimental evaluation. The experimental evaluation revealed that this approach is not only capable to show rapid prototype of wireless sensor application design, but it can also be used as a generic wireless node platform design in dynamic-adaptive reconfigurable feature, flexible, and greatly extending its applicability.